NTBI levels in C282Y homozygotes after therapeutic phlebotomy. Issue 3 (27th July 2022) - Ryan, Eleanor; Mulready, Keith; Wiegerinck, Erwin; Russell, Jennifer; Swinkels, Dorine W.; Stewart, Stephen
Abstract: C282Y homozygotes exposed to sustained elevated transferrin saturation (TS) may develop worsening clinical symptoms. This might be related to the appearance of non‐transferrin bound iron (NTBI) when TS≥50% and labile plasma iron (LPI) when TS levels reach 75–80%. In this study, NTBI levels were examined in 219 randomly selected untreated and treated C282Y homozygotes. Overall, 161 of 219 had TS ≥ 50%, 124 of whom had detectable NTBI (≥0.47 µM, 1.81 µM [0.92–2.46 µM]) with a median serum ferritin 320 µg/L (226–442 µg/L). Ninety of 219 homozygotes had TS ≥ 75%, and all had detectable NTBI (2.21 µM [1.53–2.59 µM] with a median ferritin 338 µg/L [230–447 µg/L]). Of 125 homozygotes who last had phlebotomy ≥12 months ago (42 months [25–74 months], 92 had TS levels ≥ 50%, and 70 of these had NTBI ≥ 0.47 µM (2.06 µM [1.23–2.61µM]). Twenty‐six of these 70 had a normal ferritin. Fifty‐five of 125 had TS ≥ 75%, and NTBI was detected in all of these (2.32 µM [1.57–2.77 µM]) with a median ferritin 344 µg/L (255–418 µg/L). Eighteen of these 55 had a normal ferritin. In summary, NTBI is frequently found in C282Y homozygotes with TS ≥ 50%. Furthermore, C282Y homozygotes in the maintenance phase often have TS ≥ 50% together with a normal ferritin. Therefore, monitoring the TS level during the maintenance phase is recommended as an accessible clinical marker of the presence of NTBI.